2020
DOI: 10.1108/jbim-07-2018-0210
|View full text |Cite
|
Sign up to set email alerts
|

A model of entrepreneurship education in franchising – application of outside-in marketing with a behavioural focus

Abstract: Purpose Drawing on an outside-in marketing perspective, this paper aims to outline the development, implementation, evaluation and reflection of a real-world entrepreneurship education (EE) intervention with cognitive, affective and ultimately behavioural objectives. Design/methodology/approach A specific and uniform EE program specifically targeted to current “would be” entrepreneurs who were investigating the franchising business model was developed, focusing on the behavioural outcomes. The effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 104 publications
(141 reference statements)
0
2
1
Order By: Relevance
“…The franchisee pays an initial fee as well as ongoing royalties and is mandated to adhere to strict conditions and standards (Justis and Judd, 1989). This is different from independent business owners who enjoy a considerable level of autonomy (Quach et al, 2019). We found that the relationships between customer relationship development ability and contractual restrictions and regret were different between franchisees and independent business owners.…”
Section: Further Analysescontrasting
confidence: 65%
“…The franchisee pays an initial fee as well as ongoing royalties and is mandated to adhere to strict conditions and standards (Justis and Judd, 1989). This is different from independent business owners who enjoy a considerable level of autonomy (Quach et al, 2019). We found that the relationships between customer relationship development ability and contractual restrictions and regret were different between franchisees and independent business owners.…”
Section: Further Analysescontrasting
confidence: 65%
“…According to the proximity principle, to find the posting progress of the two fuzzy sets A and B , the common forms of the posting progress include Hemming's posting progress, Euclid's posting progress, the max/min posting progress and the lattice posting progress, which are respectively shown in Eqs. ( 11), ( 12), ( 13), ( 14) and (15). 12), Eq.…”
Section: ( )mentioning
confidence: 99%
“…It was determined that the program was effective in involving students in exploring careers and stimulating their thoughts about future career development [14]. Quach, S. et al evaluated and reflected on the development of individuals in an entrepreneurship education intervention based on a marketing perspective, based on questionnaire responses, the EE intervention led to positive perceptions of the participants about relationship management, and improved B2B relationships within business networks [15]. Islam, M. N. et al evaluated a social cognitive career theory education program in Project HOPE based on baseline and follow-up evaluation data, suggesting that the program was effective in engaging students in career exploration and stimulating thinking about future career development [16].…”
Section: Introductionmentioning
confidence: 99%